2007
DOI: 10.1093/ecam/nem050
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Treatment for Low Back Pain and Lower Limb Symptoms—The Relation between Acupuncture or Electroacupuncture Stimulation and Sciatic Nerve Blood Flow

Abstract: To investigate the clinical efficacy of acupuncture treatment for lumbar spinal canal stenosis and herniated lumbar disc and to clarify the mechanisms in an animal experiment that evaluated acupuncture on sciatic nerve blood flow. In the clinical trial, patients with lumbar spinal canal stenosis or herniated lumbar disc were divided into three treatment groups; (i) Ex-B2 (at the disordered level), (ii) electrical acupuncture (EA) on the pudendal nerve and (iii) EA at the nerve root. Primary outcome measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 17 publications
3
37
0
1
Order By: Relevance
“…Acupuncture is thought to stimulate inhibitory nerve fibers for a short period, reducing transmission of pain signal to the brain [33]. Acupuncture treatment activates endogenous analgesic mechanisms [34], causing secretion of endorphin which is an endogenous opioid [35] and triggering release of adenosine [36], producing a rapidly effective analgesic action on radicular sciatica. Extensive research has shown that acupuncture analgesia may be initiated by stimulation of high-threshold, small-diameter nerves in the muscles [37].…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is thought to stimulate inhibitory nerve fibers for a short period, reducing transmission of pain signal to the brain [33]. Acupuncture treatment activates endogenous analgesic mechanisms [34], causing secretion of endorphin which is an endogenous opioid [35] and triggering release of adenosine [36], producing a rapidly effective analgesic action on radicular sciatica. Extensive research has shown that acupuncture analgesia may be initiated by stimulation of high-threshold, small-diameter nerves in the muscles [37].…”
Section: Discussionmentioning
confidence: 99%
“…For lower extremity symptoms originating from lumbar spine disease, in an investigation similar to the present study our research group has already reported on a clinical effect in about half of the patients given acupuncture treatment to the lumbar paraspinal region. 10 In addition, in animal experiments it was found that application of acupuncture to the lumbar paraspinal region increased the sciatic nerve blood flow in approximately 60% of animals. 11 It is possible that such a change would also occur in the cervical spine, which is very similar to the lumbar spine in terms of structure and innervation.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to control blood fluidity by using acupuncture showed that the acupuncture signal initiated at the acupoints was transferred to the brain through the afferent nervous pathway; therefore, it modulated the function of neurotransmitter systems such as the cardiovascular center. Output signaling cascades may improve blood fluidity through efferent neural regulation, such as that by the sympathetic nervous system [25].…”
Section: Influence Of Acupuncture Stimuli On Blood Fluiditymentioning
confidence: 99%